Chromosomally integrated human herpesvirus 6 in heart failure: prevalence and treatment. (11th November 2014) - Kühl, Uwe; Lassner, Dirk; Wallaschek, Nina; Gross, Ulrich M.; Krueger, Gerhard R.F.; Seeberg, Bettina; Kaufer, Benedikt B.; Escher, Felicitas; Poller, Wolfgang; Schultheiss, Heinz‐Peter
<x xml:space="preserve">Abstract</x> Aims Human herpesvirus 6 (HHV‐6) A and B are two betaherpesviruses that are associated with many conditions including roseola, drug‐induced hypersensitivity syndrome, limbic encephalitis, and myocarditis. HHV‐6 is integrated in the germline [chromosomically integrated HHV‐6 (ciHHV‐6)] in ∼0.8% of the human population. To date, the prevalence, species distribution, and treatment responses of ciHHV‐6 are unknown for cardiac patients. Methods and results We determined the prevalence of HHV‐6 and ciHHV‐6 genotypes in 1656 endomyocardial biopsies of patients with persisting unexplained symptoms of heart failure. Infection of cardiac tissue was identified by nested PCR, electron microscopy, and immunohistochemistry. Virus load and mRNA levels were followed in ciHHV‐6 patients treated with ganciclovir. HHV‐6 was detected in 273 of 1656 cardiac tissues (16.5%; HHV‐6B, 98.2%, HHV‐6A, 1.8%) by PCR. Nineteen of the 1656 patients (1.1%) presented with persistently high HHV‐6 copy numbers indicative of ciHHV‐6. Sequencing confirmed ciHHV‐6A in seven patients (36.8%) which was considerably higher than detected in non‐ciHHV‐6 patients. Inheritance was demonstrated in three selected families, confirming ciHHV‐6 chromosomal integration by PCR and fluorescence in situ hybridization. HHV‐6 reactivation and chromosomal integration were confirmed in peripheral blood mononuclear cells and heart tissue. Virus particles were identified in degenerating myocytes and interstitial cells. Antiviral treatment abolished viral mRNA and ameliorated cardiac symptoms. Conclusion Virus replication in cardiac tissue of ciHHV‐6 heart failure patients suggests that ciHHV‐6 reactivation causes persistence of unexplained heart failure symptoms. We demonstrated that antiviral treatment, effective in decreasing viral transcripts and clinical complaints of cardiomyopathies, is a new therapeutic option for ciHHV‐6‐associated diseases.